Teologia e teoria política: aproximações críticas entre correntes da teologia contemporânea e o pensamento político de Jürgen Habermas - Jacobsen, Eneida (2015)
Based on a dialog between the political theory of Jürgen Habermas and currents of contemporary theology, namely, liberation theology and public theology, this dissertation affirms the political-democratic potential of a theology anchored in the lifeworld for the communicative process conducted in the public sphere. The first chapter offers an introduction to the main concepts of Habermas' work and its reception in theology, highlighting the centrality of themes such as emancipation, liberation, politics and religion in the dialog between Habermas and theology. The second chapter is dedicated to the presentation of the Habermasian concept of lifeworld and of the notion of a theology developed from the lifeworld dimension. As background of all possible understanding, lifeworld constitutes a horizon of meaning reproduced through daily communicative practice. Lifeworld analyses take into consideration the intersubjective perspective of the actors themselves placed in concrete life situations. Their intersubjective worldviews are found expressed in narratives, interpretations of daily experiences, cultural and religious symbols, shared hopes and joint mobilizations. Liberation theology can be understood as a systematized effort of carrying out theological thought based on the lifeworld dimension. A theology anchored in the lifeworld uses as material for its reflection aspects of the formation of subjectivity as well as cultural and organizational expressions in society and helps, in a second moment, to channel communicative efforts of the lifeworld to the public sphere. The third chapter is dedicated to the Habermasian concept of public sphere and points out tasks for theology in this space. The public sphere is described as a communicative network which connects the lifeworld to the political system to the extent in which issues identified by people in their daily lives are thematized and problematized within it. A theology anchored in the lifeworld helps in thematizing the demands of the lifeworld into the public sphere and contributes to the task of translating religious contents into an accessible language both for religious as well as for non-religious people. Public theology, in defending the encounter of theology with different dialog partners, shows itself as a fruitful perspective for the development of theology's translating task. In its tie to the lifeworld and in its work in the public sphere, Christian theology is challenged and motivated by three main fundamental characteristics of the Judeo-Christian tradition: remembering, prophecy and liberation. The memory of suffering and liberation feeds the prophetic practice of discernment oriented to the announcement and quest of liberation in the various ambiances of human life. Finally, in the fourth chapter, the model of a theology anchored in the lifeworld and active in the public sphere is visualized with regard to different theoretical issues which permeate the dialog between Habermas and theology, with the formulation of the following theses: faith does not annul the importance of reason; the argumentative practice in the public sphere can be a means of inclusion of excluded groups; theology in the public sphere can be constructive for a political-democratic process; theologies of liberation are important in a democracy; and the materiality of ethics is not possible without its intersubjectivity while at the same time ethics is not possible without preserving the materiality of life. In general terms, from the perspective of the political theory of Habermas, the present doctoral dissertation affirms the political value of a theology anchored in the lifeworld and active in the public sphere; and from the perspective of theology it affirms the theological value of the creative word of daily life for an inclusive political process orientated toward the promotion of life in abundance for all.